"Plato Socraticus" – The Apology of Socrates and Euthyphro - Erler, Michael (Peitho. Examina Antiqua, 2011)
The present paper focuses on the two works of Plato’s first tetralogy so as to bring out and generally characterize the Socratic dimension of Plato’s philosophizing. It is common knowledge that Socrates’ trial and defense inspired Plato to engage in dialogical writing which culminated in the famous logoi Sokratikoi. The article deals with the following issues: 1. Philosophy as a ‘care for the soul’ in the Apology; 2. “The unexamined life is not worth living for a human being” (Ap. 38a); 3. Philosophy as a service to the god in the Euthyphro; 4. Socrates’ elenchos; 5. Plato’s logoi Sokratikoi. While the issues are lively debated in the subject literature, the present paper makes references to several important studies and to the broader account of Plato’s philosophy that is to be found in Erler 2006 and Erler 2007.